Development of a Dietary Factor Assessment Tool for Evaluating Associations between Visceral Fat Accumulation and Major Nutrients in Japanese Adults. (13th February 2019) - Takase, Hideto; Sakane, Naoki; Morimoto, Toshihisa; Uchida, Takanobu; Mori, Kenta; Katashima, Mitsuhiro; Katsuragi, Yoshihisa
Abstract : Background and Objectives . The increased prevalence of metabolic syndrome necessitates the establishment of tools for evaluating dietary factors associated with visceral fat accumulation and preventing visceral fat obesity. Here, we aimed to develop a dietary factor assessment tool for evaluating visceral fat accumulation. Methods . We conducted a dietary habit questionnaire survey and visceral fat measurement by bioelectrical impedance analysis in 11, 438 adults (Survey 1) and a dietary habit questionnaire survey and dietary assessment based on 3-day meal records in 579 adults (Survey 2). Dietary habit factors were identified by factor analysis with varimax rotation, and their relationship with visceral fat accumulation and major nutrients were analyzed. Results . Factor analysis of the dietary habit questionnaire revealed the following five main dietary factors: "Appetite (15 questions), " "Healthy food choice (5 questions), " "Sedentary behavior (6 questions), " "Calorie restriction (5 questions), " and "Irregular mealtime (4 questions)." "Appetite" correlated positively with visceral fat accumulation and energy intake mainly from carbohydrate. "Healthy food choice" correlated negatively with visceral fat accumulation and positively with the protein/fat ratio, dietary fiber/carbohydrate ratio, and N-3 fatty acid/fat ratio. Dietary guidance to modify excess energy intake and increase nutritional balance might be effective toward preventing visceral fat accumulation. Conclusions . The dietary factor assessment tool developed in this study can be used to diagnose problems related to dietary habits and provide guidance for dietary modifications aimed at preventing visceral fat accumulation.